The Analysis of Character Education values in Islamic Literature for teaching Language: A Descrptive Study - 'Aini, Anisa Nur (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2020)
The aim of the study is to describe the character education values in Islamic stories. The qualitative descriptive research was used in the study. Purposive random sampling was use to determine the object and content analysis was used to analyzed the data. There were nine Islamic stories in the study. The results of this research revealed that there are 15 of 18 character education in the Islamic stories, except democracy, love to read and environmental care. And the Islamic stories can be use to build a good character of generation. Islamic literatures in the form of Islamic stories gives many advantages particularly about teaching character and personality indirectly. Not only gives the awareness of islamic values, but also it provides knowledge of language and culture especially in the context of Islam. Islamic stories also provide with other filed science knowledge, such as history, math, attitude and so on.